Penerapan Metode Dempster Shafer Sistem Pakar Pada Penyakit Tuberkolosis - Kinanti Putri, Juia Choirunnisa; Kinasih, Oktavia Chairranita Putri; ., Latipah (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
The Dempster-Shafer (DS) method is a method in trust theory that is used to overcome uncertainty in decision making. An expert system that utilizes the Dempster-Shafer method can be used to diagnose tuberculosis (TB). Application of the Dempster-Shafer method in an expert system for TB requires a good understanding of the medical domain and the ability to correctly combine evidence from multiple sources. In addition, collaboration with medical experts in developing this system will increase the accuracy and usefulness of the expert system. At the Wonokromo Community Health Center, the use of websites to diagnose tuberculosis is still lacking, therefore the aim of using this website is to help the community know more about tuberculosis. In the design process, this system uses a user interface, and is equipped with HTML, CSS, Boostrap, and Java Script. The result of this research is a website-based expert system application using the website-based Dempster Shafer method, and is able to overcome the problems that exist at the Wonokromo Community Health Center. The black box testing results show that the module configuration functions well and meets user needs.